A REVIEW ON SMART SECURITY SOLUTIONS BASED ON IOT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This paper deals with the Review of design and implementation of Smart surveillance monitoring system using Raspberry pi and fingerprint sensor. It increases the usage of mobile technology to provide essential security to our homes and for other control applications. The proposed The project aims at designing an intelligent access control system based on fingerprint technology. The proposed system makes use of finger print module for authentication process and an electromechanical relay switch to control magnetic door locking system for door accessing. The system also supports with camera based image capturing technique when any wrong finger print was detected and alerts through email from wireless Wi-Fi connectivity.